Immigration as a policy instrument for an economy with an aging population: A longer-run perspective - Frank T. Denton; Byron G. Spencer (McMaster University, Research Institute for Quantitative Studies in Economics and Population (QSEP), 2014)
Population aging is a problem common to many countries: an increasing proportion of retired people, a decreasing proportion of working age, and resultant downward pressure on national product per capita. We explore longer-run aspects of immigration as a policy instrument in this context. We consider, by simulation, the importance of immigrant age distribution, proportion of child immigrants, productivity growth as an offset to aging, possible higher fertility, increased life expectancy, and greater labour force participation among older people. Our laboratory for exploration is a mythical country Alpha with a simple economy and realistic characteristics of an aging population.
Keywords: 330